STUDENT INVESTMENT BEHAVIOR: IS THERE A CORRELATION WITH RELIGIOSITY? - Faizah , Ima; Nirwana , Nihlatul Qudus Sukma (PT. Antis International Publisher, 2024)
Business developments in the technological era offer convenience, speed, and various attractive features through online shopping services equipped with easy payment services. This causes changes in people's patterns, lifestyles and behavior, becoming consumptive behavior that is not based on needs but on desires and satisfaction alone. This behavior is contrary to investment behavior as the implementation of Islamic values in terms of wealth management. Within the scope of halal finance, Islam does not only regulate how to obtain and spend assets by buying halal products, but also utilizes assets according to the designation taught by Islam. Several verses of the Qur'an and Hadith implicitly motivate people to invest. This study uses a quantitative approach with descriptive analysis. The sample of this research was students of Muhammadiyah Sidoarjo University who were randomly selected. The results showed that employment status and religiosity factors influenced student investment behavior, while age and gender had no significant effect.